The assessment of reliability generalisation of clinician-administered PTSD scale for DSM-5 (CAPS-5): a meta-analysis - Wojujutari, Ajele Kenni; Idemudia, Erhabor Sunday; Ugwu, Lawrence Ejike (Frontiers in Psychology, 2024)
The CAPS-5 is a reliable instrument for assessing PTSD symptoms, demonstrating strong consistency, validity, and reliability after a traumatic event. However, further research is warranted to explore the divergent validity of the CAPS-5 and its adaptation to diverse cultural contexts.Objective: In this meta-analysis, we endeavoured to comprehensively evaluate the reliability generalization of the CAPS-5 across diverse populations and clinical contexts.Methods: A reliability generalization meta-analysis on the psychometric properties of CAPS-5 was conducted, encompassing 15 studies. The original versions' psychometric properties were systematically retrieved from databases including PubMed, PsychNet, Medline, CHAHL, ScienceDirect, Scopus, Web of Science, and Google Scholar, with a focus on studies published between 2013 and 2023. Two independent investigators evaluated study quality using QUADAS-2 and COSMIN RB, pre-registering the protocol in the Prospero database for transparency and minimizing bias risk.Results: Meta-analysis reveals CAPS-5 global reliability (α = 0.92 (95% CI [0.90, 0.94]), z = 99.44, p < .05 across 15 studies, supporting consistent internal consistency. Subscale analysis shows variability in Reexperiencing (α = 0.82), Avoidance (α = 0.68), Cognition and Mood (α = 0.82), and Hyperarousal (α = 0.74), with an overall estimate of 0.77 (95% CI [0.70;0.83]). Language-dependent analysis highlights reliability variations (α range: 0.83 to 0.92) across Brazilian-Portuguese, Dutch, English, French, German, Korean, and Portuguese. Test-retest reliability demonstrates stability (r = 0.82, 95% CI [0.79; 0.85]), with overall convergent validity (r = 0.59, 95% CI [0.50;0.68]).The meta-analysis affirms CAPS-5's robust global and subscale reliability across studies and languages, with stable test-retest results. Moderator analysis finds no significant impact, yet substantial residual heterogeneity remains unexplained. Our findings contribute intricate insights into the psychometric properties of this instrument, offering a more complete understanding of its utility in PTSD assessment.